Analisis Faktor-Faktor Yang Memengaruhi Kualitas Laporan Keuangan Pemerintah Daerah Pada Badan Pendapatan Daerah Kabupaten Sinjai - Al Ansari, Andi Khafifah Khairun; Dunakhir, Samirah; Samsinar (Yayasan Sagita Akademia Maju, 2024)
This research aims to analyze the influence of the application of regional government accounting standards, regional financial accounting systems and human resource competence on the quality of regional government financial reports at BAPENDA Sinjai Regency. Sampling was carried out using purposive sampling. The respondents in this research were 30 employees of BAPENDA Sinjai Regency and 1 user of financial reports addressed to members of the DPRD. The data collection technique is using a questionnaire, and analyzed using descriptive statistics, data quality testing, classical assumption testing, multiple regression analysis, and hypothesis testing. The data that has been collected is processed using SPSS 29. The results of this research show that the application of regional government accounting standards, the application of regional financial accounting systems, and human resource competence have a positive and significant effect on the quality of regional government financial reports at BAPENDA Sinjai Regency.